Contribution of sustainable street vending to municipal solid waste management in Tanzania: A case of Morogoro Municipality - Apolo, Didas (Mzumbe University, 2023)
This study provides an over view on the contribution of sustainable street vending to the municipal solid waste management in Tanzania a case of Morogoro Municipality. The main objective of this study was to determine the contribution of sustainable street vending to municipal solid waste management in Tanzania. The specific objectives were to examine the perception of street vendors on municipal solid waste management in Morogoro Municipality, to assess strategies used by street vendors to mitigate solid waste production in Morogoro Municipality, to assess strategies used by the Municipal government to ensure Sustainable street vending for sustainable SWM in Morogoro Municipality and to determine street vendors involvement in solid waste management in Morogoro Municipality. Mixed methods research design was employed. Questionnaires, interview and observation methods were used in data collection. The study had a sample of 96 respondents from: street venders, environmental officers, ward health officers and sweeper leaders. Probability and non-probability sampling were used in which quasi-simple random was used to obtain a sample of street venders and purposive sampling was applied to obtain the key informants. Data were analyzed by using both quantitative and qualitative methods. Quantitative descriptive analysis was done using frequencies and percentage, while qualitative employed content analysis. The findings revealed that street venders were not willing to participate in municipal solid waste management due to their negative perception towards the municipal solid waste management. The majority of street venders were found to have low level of knowledge on solid waste management. They also, neither had ID nor license as a strategy that contributes to sustainable municipal solid waste management in Morogoro Municipality. The study findings contribute to the knowledge on how municipals can mobilize resources for sustainable solid waste management. The study recommended that knowledge on solid waste management should be provided to street venders for the purpose of influencing them to participate in municipal solid waste management. Lastly municipal council should develop and implement well integrated solid waste management action plan by involving street venders.